Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

Universities, inclusive development and social innovation: an international perspective - Brundenius, Claes; Göransson, Bo; Mello, Jose Manoel Carvalho de (Springer, 2017)
This book examines the ways in which universities can play a crucial role in inclusive development, social innovation and social entrepreneurship. It aims to prove the importance of inclusive development and inclusive innovation on economic growth and demonstrate the ways in which universities can be pioneers in this area through initiatives in social responsibility and social innovation. For example, providing access to a university education without discrimination of race, gender, income status, or other factors would help to diminish the increasing income differentials currently being experienced in many countries, especially in the developing world. The research and studies included in this book provide insight into possible actions that can be taken by universities and public and private shareholders in inclusive development, social innovation, social entrepreneurship and overall regional economic and social development.
Keywords: Développement inclusif; Développement social; Entrepreneuriat social; Innovation inclusive; Innovation sociale; Inégalités; Réservé UdeM; Rôle des universités; Université

Universities, inclusive development and social innovation: an international perspective - Brundenius, Claes; Göransson, Bo; Mello, Jose Manoel Carvalho de (Springer, 2017)
This book examines the ways in which universities can play a crucial role in inclusive development, social innovation and social entrepreneurship. It aims to prove the importance of inclusive development and inclusive innovation on economic growth and demonstrate the ways in which universities can be pioneers in this area through initiatives in social responsibility and social innovation. For example, providing access to a university education without discrimination of race, gender, income status, or other factors would help to diminish the increasing income differentials currently being experienced in many countries, especially in the developing world. The research and studies included in this book provide insight into possible actions that can be taken by universities and public and private shareholders in inclusive development, social innovation, social entrepreneurship and overall regional economic and social development.
Keywords: Développement inclusif; Développement social; Entrepreneuriat social; Innovation inclusive; Innovation sociale; Inégalités; Réservé UdeM; Rôle des universités; Université